Downlink power control performance in (E)GPRS networks - Rodriguez, R.; Martinez, J.; Romero, J. (Proceedings IEEE 56th Vehicular Technology Conference, 2002)
The progressive introduction of packet switched (PSW) services in GSM networks sharing the same physical resources involves interference control techniques that preserve the quality of speech communications. This article presents a downlink power control (DLPC) algorithm for (E)GPRS that considerably reduces the interference introduced by PSW in mixed environments, notably increasing the system capacity around 32% for EGPRS, 50% for GPRS (CS1 and CS2) and 33% for GPRS (from CS1 to CS4).